Redescription and a new synonym of the spider Pachygnatha amurensis Strand, 1907 (Araneae, Tetragnathidae, Tetragnathinae) - Marusik, Yuri M.; Azarkina, Galina N.; Omelko, Mikhail M. (Zootaxa, 2015)
Pachygnatha Sundevall, 1823, with 43 species, is the second largest genus in the subfamily Tetragnathinae. This genus occurs in the Holarctic, Africa, South and South-East Asia (WSC 2015). One quarter of its species are known from a single sex: four species are known from females and seven from males. While studying Tetragnathidae of the Far East Marusik (1989) reported over a dozen specimens belonging to Pachygnatha amurensis Strand, 1907, a species previously known from the holotype male and the original description, which was not illustrated. Recently, Pachygnatha gaoi Zhu et al., 2003 (Marusik et al. 2007) was reported from environs of Khabarovsk as a species new to Russia. Comparison of specimens identified as P. amurensis (through comparison with the holotype male) and P. gaoi revealed that they belong to the same species and the two names should be synonymised. The main goals of this paper are to provide detailed figures of P. amurensis, to synonymize P. gaoi known from both sexes and to survey the distribution of this species.